Undernutrition and associated factors among adult prisoners in Fiche town, central Ethiopia: a facility-based cross-sectional study - Wondimu, Mengistu; Siyoum, Ayichew; Ketema, Indeshaw; Goshu, Abel Tibebu; Habte, Sisay; Mehadi, Ame; Ayele, Behailu Hawulte (Frontiers in Nutrition, 2023)
Background: Undernutrition is a major public health problem, particularly in many developing countries. Nutritional problems are frequently overlooked in low-income countries, especially among vulnerable populations such as imprisoned people. The scientific data on the rate of undernutrition among imprisoned people are limited in Ethiopia. Hence, this study aimed to assess the magnitude and determinants of undernutrition among prisoners in Fitche town, Central Ethiopia. Methods: A facility-based cross-sectional study was conducted from August 15 to September 15, 2020. A systematic random sampling technique was used to select participants. All prisoners whose age was 18 years and above who have been in prison for at least six months were included. Data were collected using interviewer-administered pretested semi-structured questionnaires and standard anthropometric measurements. A cut-off point of body mass index < 18.5kg/m2 was used to measure undernutrition. Data were coded and entered into Epi-data version 3.1 and analyzed using Statistical Package for Social Sciences version 20.0. Binary logistic regression analysis was conducted to identify factors associated with undernutrition. Adjusted odds ratio with 95% confidence interval was used to measure the strength of the association and statistical significance was declared at p-value <0.05. Results: The overall magnitude of undernutrition among prisoners was 20%(95%CI: 16.5, 23.6). Duration of imprisonments; 25 to 59 months [AOR=3.07; 95%CI: 1.33,7.04] and greater than 59 months [AOR=4.56; 95%CI: 2.0,10.45], and depression; mild and moderate [AOR=1.9; 95%CI: 1.05,3.45] and moderately severe and severe [AOR=2.78; 95%CI: 1.17,6.60] were significantly associated with increased odds of undernutrition. However, being female [AOR=0.51; 95%CI: 0.26,0.98], having financial support [AOR=0.36; 95%CI: 0.15,0.87], engaged in income-generating work [AOR=0.27; 95%CI: 0.15,0.40], and dietary diversity; medium [AOR=0.35; 95%CI: 0.15,0.80] and good [AOR=0.23; 95%CI: 0.08,0.61] were significantly decreased the odds of undernutrition. Conclusion: The magnitude of undernutrition among prisoners was found to be high. One in five prisoners was undernourished in Fitche town prison. Sex, financial support, duration of imprisonment, income-generating work, dietary diversity, and depression were significant predictors of undernutrition. Access to healthy food and diversified diets should be ensured for prisoners, implement early screening and treatment of depression, and encourage prisoners to participate in income-generating work within the prison.